Palatal Enlargement in Chronic Lymphocytic Leukemia - Vibhute, P.; Carneiro, E.; Genden, E.; Som, P.M. (American Journal of Neuroradiology, 2006)
SUMMARY: Palatal involvement in chronic lymphocytic leukemia (CLL) is rare and has only been reported 3 previous times in the non-radiology literature. To our knowledge this is the first imaging description of this entity. Based on our experience, when smoothly lobulated, homogeneous masses are identified on the oral surface of the hard palate, the diagnosis of CLL should be considered.